Adult-Onset Xanthogranuloma With Frontal Nerve and Intracranial Involvement. Issue 5 (12th March 2021) - Shapira, Yinon; Juniat, Valerie; Smith, Caroline; Selva, Dinesh
Abstract : Adult-onset xanthogranuloma (AOX) typically affects the preseptal and anterior orbital regions. The authors report a 49-year-old man with a 6-month history of unilateral AOX, demonstrating diffuse extraconal and intraconal orbital involvement, including the lacrimal gland and extraocular muscles. There was frontal nerve enlargement, intracranial and pterygopalatine fossa involvement. Investigations excluded IgG4 disease and Erdheim–Chester disease. This case illustrates that AOX may be added to the causes of orbital nerve enlargement and may demonstrate intracranial extension. Abstract : This case represents an atypical, locally extensive presentation of adult-onset xanthogranuloma, in association with frontal nerve enlargement and intracranial involvement. Supplemental Digital Content is available in the text.